2018
DOI: 10.1002/lsm.22823
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of human dermal fibroblast subpopulations to visible and near‐infrared light: Potential of photobiomodulation for addressing cutaneous conditions

Abstract: This study highlights a differential impact of light on human skin cells with upregulation of metabolic activity with NIR light, and inhibition of pro-collagen production and proliferation in response to blue light. These findings open-up new avenues for developing therapies for different cutaneous conditions (e.g., treatment of keloids and fibrosis) or differential therapy at distinct stages of wound healing. Lasers Surg. Med. 50:859-882, 2018. © 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 76 publications
(150 reference statements)
3
36
0
1
Order By: Relevance
“…Whereas blue light is cytotoxic for keratinocytes, dermal fibroblasts and skin‐derived endothelial cells at short wavelengths (410‐420 nm), and high fluences, it inhibits cell proliferation and induces differentiation at lower fluences and/or higher wavelengths (up to 480 nm) dose‐dependently, presumably by photolytic release of NO . Furthermore, papillary and reticular fibroblasts respond differently to high‐dose blue light, for example, with regard to their metabolic activity . Accordingly, an opsin receptor (peropsin) sensitive for blue‐violet light was identified on human keratinocytes and fibroblasts, and opsin receptor expression was disrupted by blue light irradiation along with an oxidative stress response .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Whereas blue light is cytotoxic for keratinocytes, dermal fibroblasts and skin‐derived endothelial cells at short wavelengths (410‐420 nm), and high fluences, it inhibits cell proliferation and induces differentiation at lower fluences and/or higher wavelengths (up to 480 nm) dose‐dependently, presumably by photolytic release of NO . Furthermore, papillary and reticular fibroblasts respond differently to high‐dose blue light, for example, with regard to their metabolic activity . Accordingly, an opsin receptor (peropsin) sensitive for blue‐violet light was identified on human keratinocytes and fibroblasts, and opsin receptor expression was disrupted by blue light irradiation along with an oxidative stress response .…”
Section: Discussionmentioning
confidence: 91%
“…14,77 Furthermore, papillary and reticular fibroblasts respond differently to high-dose blue light, for example, with regard to their metabolic activity. 78 Accordingly, an opsin receptor (peropsin) sensitive for blue-violet light was identified on human keratinocytes 79 and fibroblasts, 80 and opsin receptor expression was disrupted by blue light irradiation along with an oxidative stress response. 81 In line with these findings, Regazzetti et al 82 identified opsin 3 as the key sensor in melanocytes responsible for hyperpigmentation induced by blue light (reviewed by 47 ).…”
Section: F I G U R Ementioning
confidence: 99%
“…Tissue contraction can be observed in a total skin graft and occurs when the graft is integrated into its receptor bed, promoting the action of myofibroblasts (granulation tissue fibroblasts) and contractile proteins, which have a retractile function in the contraction of wounds . Excessive contraction might damage the graft due to the restricted mobility of the joints involved, which leads to an unsatisfactory functionalresult.…”
Section: Discussionmentioning
confidence: 99%
“…Integration of a skin graft will depend on the perfusion, adhesion, and viability of the transferred skin segment, which will depend directly on vascularization. It is known that integration of a skin graft is one of the main challenges in this procedure . Using a method for evaluating the same, through histological analysis with hematoxylin and eosin staining, the aim was to observe the gap formed between the graft and its bed.…”
Section: Discussionmentioning
confidence: 99%
“…Human sight is dependent on visible radiation (light) that is also important for setting circadian rhythms. Infrared radiation may have potential for the biomodulation of fibroblasts for treatment of cutaneous conditions . We have a good understanding of the cellular and clinical consequences of direct photodamage by sunlight caused when the cutaneous chromophore (radiation absorbing molecule) is the target molecule (e.g.…”
mentioning
confidence: 99%